CONTROL SYSTEMS IN OUR DAILY LIFE - Rohani Jahja Widodo (Universitas Ahmad Dahlan, 2007)
This paper presents development and applications of Control Systems (CS). Several characteristics of CS can be linked to human behavior. CS can